2004
DOI: 10.1074/jbc.m400655200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antagonistic Potency of Transforming Growth Factor-β Receptor Extracellular Domains by Coiled Coil-induced Homo- and Heterodimerization

Abstract: Transforming growth factor-␤ (TGF-␤) plays a causal role in several human pathologies including fibrotic diseases and metastasis. TGF-␤ signaling is mediated through its interaction with three types of cell surface receptors, RI, RII, and RIII. The soluble ectodomains of RII and RIII bind to TGF-␤, making them attractive candidates to sequester TGF-␤ and inhibit its activity. To optimize the activity of the ectodomains, we studied the effect of artificially dimerizing them upon their kinetics of binding to TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
5
23
1
Order By: Relevance
“…Corroborating data from a biological inhibition assay of TGF-␤ activity in cells were consistent with the selectivity and specificity of sT␤RII.Fc and sT␤RII-B.Fc seen in the binding data. Our measured binding affinities (30 to 500 pM) are consistent with previously published affinities for the ECD of T␤RII (31,36,37), and compare well with indirect estimates for membrane-bound complexes (1).…”
Section: Discussionsupporting
confidence: 76%
“…Corroborating data from a biological inhibition assay of TGF-␤ activity in cells were consistent with the selectivity and specificity of sT␤RII.Fc and sT␤RII-B.Fc seen in the binding data. Our measured binding affinities (30 to 500 pM) are consistent with previously published affinities for the ECD of T␤RII (31,36,37), and compare well with indirect estimates for membrane-bound complexes (1).…”
Section: Discussionsupporting
confidence: 76%
“…the generation of mini-antibodies [41,42], the assembly of receptor ectodomain subunits [9,19,[43][44][45], and as an affinity tag system for purification and biosensor applications [8][9][10][46][47][48]. Immobilized EGF has been shown to be more mitogenic for CHO cells than soluble EGF [29], perhaps due to decreased ligand inter- nalization and degradation [30].…”
Section: Discussionmentioning
confidence: 99%
“…as a tag for purification purposes or for induced protein-protein interaction studies. We have shown previously using SPR-based biosensor studies that E5 or K5-coil-tagged receptor ectodomains (from the transforming growth factor (TGF)-b Types II and III receptors) bind TGF-b similarly to untagged receptor ectodomains, and that the coil tags can be used for receptor capture on the biosensor surface [9,10]. More recently, we used the E/K coiled-coil dimerization system to establish a virus retargeting scheme in which E5-coil-EGF was utilized to retarget K4-coil-expressing adenovirus to EGFR expressing cells [11].…”
mentioning
confidence: 99%
“…However, modeling studies of TGF-␤ superfamily receptors suggest that the type I and type II receptors exist as multimers in cells even in the absence of ligand (15). It was recently shown that, when obligated to form dimers through addition of heterologous coiledcoil domains, the affinity of sT␤RII and sT␤RIII for TGF-␤ was increased such that biological antagonism could be observed (36). Interestingly, the expression system used for the present studies utilizes a portion of the human Fc chain that contains a free cysteine, resulting in the receptor-Fc fusion proteins being secreted as dimers.…”
Section: Fig 2 Representative Binding Results and Scatchard Analysimentioning
confidence: 99%